Liver transient elastography values in healthy South African children - Penelope C. Rose; Mark F. Cotton; Kennedy Otwombe; Steve Innes; Etienne D. Nel (BMC, 2023)
Abstract Background Transient elastography (TE) is a rapid noninvasive ultrasound-based technology that measures liver stiffness as a surrogate for liver fibrosis and controlled attenuation parameter (CAP) as a measure of liver steatosis. However, normal ranges in children are not well defined in all populations. The aim of this study was to determine transient elastography values in healthy South African children. Methods From April 2019 to December 2021, children were recruited from the HIV negative control group of a cohort study. Only children neither overweight nor obese, without evidence of liver disease, no medical condition or medication associated with hepatic steatosis or fibrosis and normal metabolic profile were included in this cross-sectional analysis. Clinical data, anthropometry and blood samples were collected on the same day as transient elastography with controlled attenuation parameter was performed. Results 104 children (median age 12.8 years [IQR 11.4-14.8, range 7.9-17.7 years]; 59 [57%] boys) were included. Liver stiffness was positively correlated with age (Pearson's r = 0.39, p < 0.001). Median liver stiffness in boys (5.2 kPa [5th to 95th percentiles 3.6 to 6.8 kPa]) was greater than in girls (4.6 kPa [5th to 95th percentiles 3.6 to 6.1 kPa; p = 0.004]), but there was no difference by ethnicity. Median CAP was 179dB/m (5th to 95th percentiles 158 to 233dB/m). There was a positive correlation between CAP and body mass index (BMI) z-score, but no difference by age, sex, ethnicity or pubertal status. Conclusion Liver stiffness values increase with age and are higher in healthy South African boys than girls, whereas CAP values vary with BMI, but not with age or sex.